Responden Peserta Didik Dan Guru Terhadap Kemampuan Berpikir Kritis Siswa Di SMAN 7 Pekanbaru - Windy Martuty; Sepita Ferazona; Nurkhairo Hidayati (Jurnal Pendidikan Sains dan Teknologi Terapan | E-ISSN : 3031-7983, 2025)
Student and Teacher Respondents on Students' Critical Thinking Skills at SMAN 7 Pekanbaru, This study aims to determine the respondents of teachers and students in critical thinking at SMAN 7 Pekanbaru in the 2024/2025 academic year. The type of data in this study is a type of qualitative descriptive data, the sample in the study used simple random sampling, where the sample in this study was taken randomly, where only 1 student was taken from each class. The data obtained in this study were in the form of interview results to determine the responses of teachers and students of class XI SMAN 7 Pekanbaru to critical thinking skills. Based on the results of the study, it showed that teachers used a systematic evaluation method and focused on developing students' critical thinking skills. The evaluation given is based on questions that are already in the textbook. This approach not only emphasizes the final result, but also pays attention to the student learning process. Based on student interviews, it was shown that teachers routinely conduct evaluations with various approaches in compiling questions. Although the evaluation results were considered quite good, there are still opportunities to improve quality, especially in supporting students who face difficulties.